2016
DOI: 10.1021/acs.molpharmaceut.6b00217
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and Brain Pharmacokinetics of Perforin Inhibitor Prodrugs

Abstract: We have recently reported that by converting a perforin inhibitor into an l-type amino acid transporter 1 (LAT1)-utilizing prodrug its cellular uptake can be greatly increased. The aim of the present study was to determine the in vivo and brain pharmacokinetics of two perforin inhibitors and their LAT1-utilizing prodrugs 1 and 2. In addition, the brain uptake mechanism and entry into primary mouse cortical neurons and astrocytes were evaluated. After 23 μmol/kg i.p. bolus injection, the prodrugs' unbound area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 34 publications
3
46
0
Order By: Relevance
“…The half-life of the bioconversion of the amide derivative 2 was up to 10 times higher compared with that of the ester 1. As with other reports, the result indicates that the amide bond is less sensitive to enzymatic hydrolysis than the corresponding ester bond [2,24]; the ester derivative is more susceptible to enzymatic bioconversion, limiting its ability to reach the target site intact in vivo.…”
Section: Discussionsupporting
confidence: 84%
“…The half-life of the bioconversion of the amide derivative 2 was up to 10 times higher compared with that of the ester 1. As with other reports, the result indicates that the amide bond is less sensitive to enzymatic hydrolysis than the corresponding ester bond [2,24]; the ester derivative is more susceptible to enzymatic bioconversion, limiting its ability to reach the target site intact in vivo.…”
Section: Discussionsupporting
confidence: 84%
“…The high concentration of prodrug 5 in both brain and liver can be achieved due to its utilization of other transporters such as organic anion-transporting polypeptides (OATPs) which are expressed in these tissues. [23,29] Previously, we revealed that OATPs were involved in the transport of LAT1-utilizing prodrugs of perforin inhibitors [17]. In summary, the data emphasizes that the small structural changes in prodrugs designed to utilize LAT1 introduce significant effects on their brain and systemic pharmacokinetics, either enhancing or limiting the brain distribution of the parent drug.…”
Section: Accepted Manuscriptmentioning
confidence: 87%
“…Based on these features, it has been demonstrated that several prodrugs have an ability to bind to LAT1 and exploit this transporter for BBB permeation or/and cell uptake [5][6][7][8][9]16]. However, there is limited information about systemic and brain pharmacokinetics of these prodrugs including the distribution of the prodrugs and their parent drugs in the liver and their first pass metabolism [5,8,16,17].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The in situ rat brain perfusion technique demonstrated that prodrugs 77 – 79 significantly inhibited the cellular uptake of l -[ 14 C]-leucine (91.4 ± 1.6%, 75.7 ± 1.8% and 88.3 ± 2.3%, respectively), while prodrugs 80 and 81 showed minor reduction of l -[ 14 C]-leucine uptake (17.6 ± 6.7% and 6.2 ± 2.2%, respectively). In a study using the in situ rat brain perfusion technique, valproic acid prodrugs 82 and 83 and perforin inhibitor prodrugs 84 and 85 showed 16%, 81%, 97.4% and 59.4% inhibition of l -[ 14 C]-leucine uptake, respectively [ 121 , 122 ]. The studies described here have demonstrated that natural substrates of LAT1 can serve as an excellent template to enhance the delivery of small molecules into the brain.…”
Section: Lat1-mediated Prodrug Deliverymentioning
confidence: 99%